A Review of Sustainability Concepts in Marine Spatial Planning and the Potential to Supporting the UN Sustainable Development Goal 14 - Kirkfeldt, Trine Skovgaard; Frazão Santos, Catarina (Frontiers in Marine Science, 2021)
Ecosystems all over the world are under increasing pressure from human uses. The UN Sustainable Development Goal 14 (UN SDG 14) seeks to ensure sustainability below water by 2020; however, the ongoing biodiversity loss and habitat deterioration challenge the achievement of this goal. Marine Spatial Planning (MSP) is a developing practice with a similar objective to the UN SDG 14, albeit research shows that most MSP cases prioritize economic objectives above environmental objectives. This paper presents an assessment of how MSP can contribute to achieving the UN SDG 14. Results are presented in three steps. First, a representative definition of MSP is presented. Secondly, activities that can be addressed through MSP are laid out. Lastly, results are used to assess how MSP can contribute to the achievement of the UN SDG 14 targets and indicators. This assessment shows great potential for MSP to play a role in the achievement of the UN SDG 14.